Involvement of N-terminal-extended Form of Sphingosine Kinase 2 in Serum-dependent Regulation of Cell Proliferation and Apoptosis - Okada, Taro; Ding, Guo; Sonoda, Hirofumi; Kajimoto, Taketoshi; Haga, Yuki; Khosrowbeygi, Ali; Gao, Sanyang; Miwa, Noriko; Jahangeer, Saleem; Nakamura, Shun-ichi (The Journal of biological chemistry, 2005)
Sphingosine kinase (SPHK) 1 is implicated in the regulation of cell proliferation and anti-apoptotic processes by catalyzing the formation of an important bioactive messenger, sphingosine 1-phosphate. Unlike the proliferative action of SPHK1, another isozyme, SPHK2, has been shown to possess anti-proliferative or pro-apoptotic action. Molecular mechanisms of SPHK2 action, however, are largely unknown. The present studies were undertaken to characterize the N-terminal-extended form of SPHK2 (SPHK2-L) by comparing it with the originally reported form, SPHK2-S. Real-time quantitative PCR analysis revealed that SPHK2-L mRNA is the major form in several human cell lines and tissues. From sequence analyses it was concluded that SPHK2-L is a species-specific isoform that is expressed in human but not in mouse. At the protein level it has been demonstrated by immunoprecipitation studies that SPHK2-L is the major isoform in human hepatoma HepG2 cells. SPHK2-L, when expressed in human embryonic kidney (HEK) 293 cells, did not show any inhibition of DNA synthesis in the presence of serum, whereas it showed marked inhibition in the absence of serum. Moreover, serum deprivation resulted in the translocation of SPHK2-L into the nuclei. In addition, serum deprivation induced SPHK2-L expression in HEK293 cells. Furthermore, suppression of SPHK2 by small interfering RNA treatment prevented serum deprivation- or drug-induced apoptosis in HEK293 cells. Taken together, these results indicate that a major form of SPHK2 splice variant, SPHK2-L, in human cells does not inhibit DNA synthesis under normal conditions and that SPHK2-L accumulation in the nucleus induced by serum deprivation may be involved in the cessation of cell proliferation or apoptosis depending on the cell type.